TABLET FORMULATION FROM MENIRAN (PHYLLANTHUS NIRURI L.) EXTRACT WITH DIRECT COMPRESSION METHOD - Mustarichie, Resmi; Priambodo, Dradjad (International Journal of Applied Pharmaceutics, 2018)
Objective: The aim of the present study was to obtain an optimized formula of meniran (Phyllanthus niruri L.) extract tablets that fulfilled the requirements as a good pharmaceutical preparation based on Indonesian Pharmacopoeia IV and USP XVII. Methods: P. niruri plant was collected and determined at the Laboratory of Plant Taxonomy, Universitas Padjadjaran. First performed phytochemical screening to determine the content of secondary metabolites. Then designed five kinds of tablet formulas of P. niruri extract using a direct compressed method with a variation of concentration of filler. Each formula contains a similar concentration of P. niruri extract as the active ingredient, avicel PH 102 and amprotab with varying concentrations as filler, talcum, and magnesium stearate as a lubricant and Aerosil®200 vv as an adsorbent. Tablet print mass and quality of the resulting tablets were then evaluated. Also, check whether the resulting tablets still contain P. niruri extract as the active substance or not. Results: The results of phytochemical screening of simplicia and viscous plant extract showed the presence of alkaloids, polyphenols, tannins, and flavonoids as secondary metabolites. The five formulas made contain avicel PH 102 and amprotab as binders and crushers and the expected results such as shape and durability as desired. The results of examination of shrinkage rate of mass drying of tablet prints from the above five formulas indicated an increase of value from formula A (5.4609 %) to formula E (5.8600%). This was because avicel PH 102 and amprotab had a considerable moisture content, so with the combination of both fillers could increase the water content from mass print tablets. Real density, compact density, and true density decreased from formula A to formula E. The amount of these densities were influenced by the shape and size of the particles. Flowability increased from formula A (23.7124°) to formula E (26.4210°) whereas compressibility increased from formula A (21.7222%) to formula E (29,4121%). Flowability and compressibility increase might be due to the uniformity of the particle size between the amprotabs and the other additives which could cause electrical charges to the print mass affecting the speed and flow of the print mass. All quality testing results including Weight (mg), Thickness (mm), Diameter (mm), Hardness (N), Friability (%) and Disintegration time (min.) had met the requirements. Thin Layer Chromatography showed that the resulting tablets still contain P. niruri extract as the active substance. Conclusion:. Overall results showed that the formulation fulfilled the requirements as a good pharmaceutical preparation based on Indonesian Pharmacopoeia IV and USP XVII.